Integration of hatha yoga and evidence‐based psychological treatments for common mental disorders: An evidence map - O'Shea, Melissa; Capon, Hannah; Evans, Subhadra; Agrawal, Jyotsna; Melvin, Glenn; O'Brien, Jennifer; McIver, Shane (Journal of clinical psychology, 2022)
Background Interest in the use of yoga to enhance engagement with and augment the benefits of psychological treatment has grown. However, a systematic approach to reviewing existing research examining the use of yoga with psychological treatment is lacking. Materials and Methods This mapping review identified and synthesised research trialling yoga as an integrated or adjunct therapy with evidence‐based psychological interventions for the treatment of anxiety, depression, PTSD, and eating disorders. Results Overall, the review identified ten published and three unpublished studies, representing either single group or small quasi‐experimental research designs. Discussion Limited but promising findings were shown for yoga with CBT for anxiety and depression, and the integration of yoga within intensive treatment models for PTSD. Conclusions Future research is encouraged to focus on controlled trials that enable examination of the component effect of yoga when applied with evidence‐based psychological treatment and acceptability and feasibility data to further knowledge regarding a role for yoga in clinical practice.